(untitled) (Bangladesh Journal of Anatomy, 2016)
Context: The accessory mandibular foramen is an important anatomical land mark and provides pathway for additional branch of inferior alveolar nerve and vessels. Adequate anaesthesia is a prerequisite of most of the dental procedures. Effective pain control in dentistry may be achieved by the local anaesthetic techniques; the most common procedures which are followed by the inferior alveolar nerve block. Therefore, identification of accessory mandibular foramen is important for dental surgeons in nerve block and surgical procedures to avoid injury to neurovascular bundle. The aim of this study was to observe of the accessory mandibular foramen around mandibular foramen on the medial side of mandibular ramus. In 185 dry adult human mandibles. Materials and Methods: A cross-sectional, analytical type of study was conducted in the department of Anatomy, Dhaka Medical College, Dhaka from July 2010 to June 2011. The mandibles were observed for the presence of accessory mandibular foramen. (figure 1). Results: The accessory mandibular foramen were present in 6.49% of mandibles. Bangladesh Journal of Anatomy July 2016, Vol. 14, No. 2, pp. 43-44